Paint particles are a distinct and variable substrate for marine bacteria. (September 2019) - Tagg, Alexander S.; Oberbeckmann, Sonja; Fischer, Dieter; Kreikemeyer, Bernd; Labrenz, Matthias
Abstract: While paint particles are an important part of the microplastic sphere, they have, as yet, received much less research coverage, particularly regarding microplastic-microbiological interactions. This study investigated the biofilm communities of a variety of paint particles from brackish sediment using 16S rRNA gene sequencing. Paint particle biofilm communities appear to be distinct from natural (water and sediment), non-synthetic particle (cellulose) and common microplastic biofilm communities. Notably, there appears to be 1 group of sulphate-reducing bacteria from the Desulfobacteraceae family, Desulfatitalea tepidiphilia, that dominate certain paint biofilms. Of the 8 investigated paint-associated communities, four paints displayed this high Desulfobacteraceae presence. However, it is currently unclear from the chemical analysis performed of the paint surface chemistry (ATR FT-IR spectroscopy, Raman spectroscopy, SEM-EDX) what the drivers behind this might be. As such, this study provides important insights as the first to analyse microplastic-paint biofilm communities and paves the way for future research. Highlights: Paint particles biofilm communities are distinct from other substrates. Paint biofilm communities have greater similarity than other microplastics. Variability of paint biofilm communities are not described by surface chemistry. Desulfatitalea is a key player in paint particle biofilms. Paint particles may have an effect on sediment sulphur cycles.